Teacher learning in language teaching - Freeman, Donald; Richards, Jack C., eds. (New York :Cambridge University Press, 1996)
Sus temas principales son: Beginning: starting out in language teaching. Transitions: learning in the practice of teaching. Learning to teach: the role of language teacher education
Incluye bibliografía
Keywords: Lenguaje - Adiestramiento en escritura